Review paperInterleukin-17 in human inflammatory diseases - Shabgah, Arezoo Gowhari; Fattahi, Ebrahim; Shahneh, Fatemeh Zare (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Human Th17 pro-inflammatory cells are currently defined as cells that produce IL-17A and F, tumor necrosis factor (TNF)-α, IL-6, IL-21, IL-22 and IL-23. Recently discovered related molecules are forming a family of cytokines, the IL-17 family, IL-17A, IL-17B, IL-17C, IL-17D, IL-17E and IL-17F. The associated receptors for the IL-17 family identified are IL-17R, IL-17RH1, IL-17RL (receptor like), IL-17RD and IL-17RE. This review introduces the roles of IL-17 and Th17 cells in human autoimmune diseases. Studies have shown that T cells with inflammatory effects on epithelial, endothelial and fibroblast cells express IL-17. Th17 cells are supposed to be involved in various autoimmune diseases, such as rheumatoid arthritis, psoriasis, multiple sclerosis, and inflammatory bowel diseases. Base on the biologic functions and regulation, IL-17 has regulatory roles in host defense and chronic inflammation which result in tissue damage and autoimmunity. So the IL-17 links links innate and adaptive immunity and has both beneficial and pathological effects on the immune system. This paper will focus on the possible roles of IL-17 in autoimmune diseases, a fundamental player in immune regulation.